2019
DOI: 10.1007/s11357-019-00077-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity, aging, and muscle contractility: does fiber type matter?

Abstract: Sarcopenia is a universal characteristic of the aging process and is often accompanied by increases in whole-body adiposity. These changes in body composition have important clinical implications, given that loss of muscle and gain of fat mass are both significantly and independently associated with declining physical performance as well as an increased risk for disability, hospitalizations, and mortality in older individuals. This increased fat mass is not exclusively stored in adipose depots but may become d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 88 publications
0
40
1
Order By: Relevance
“…The rapid SM energetic decline is associated with significantly reduced mitochondrial oxidative capacity and markedly increased muscle fat accumulation. Although our data do not answer the question of whether mitochondrial abnormalities cause fatty accumulation or vice versa, they suggest that fatty replacement of SM and the previously described proinflammatory state ( 50 ) contribute to impaired SM HEP metabolism possibly through paracrine effects ( 51 53 ) and, in turn, increased fatigability in age-related frailty.…”
Section: Discussioncontrasting
confidence: 87%
“…The rapid SM energetic decline is associated with significantly reduced mitochondrial oxidative capacity and markedly increased muscle fat accumulation. Although our data do not answer the question of whether mitochondrial abnormalities cause fatty accumulation or vice versa, they suggest that fatty replacement of SM and the previously described proinflammatory state ( 50 ) contribute to impaired SM HEP metabolism possibly through paracrine effects ( 51 53 ) and, in turn, increased fatigability in age-related frailty.…”
Section: Discussioncontrasting
confidence: 87%
“…Aberrant cell signaling pathways in cancer are common. Activation and mutations of PI3 kinase (PI3K), mTOR, insulin-like growth factor (IGF-1), epidermal growth factor receptor (EGFR), and NF-kB pathways have all been identified in several human disorders (Lewis et al, 2018;Souder and Anderson, 2019;Carter et al, 2019;Farias Quipildor et al, 2019), especially cancer (Hanahan and Weinberg, 2011;Royce et al, 2019). IGF-1 is a ligand for receptor tyrosine kinases Abbreviations: ATCC, American Type Tissue Culture; BLI, bioluminescence intensity; BDNF, brain derived neurotrophic factor; DAPI, 4′,6-diamidino-2phenylindole; DMSO, Dimethyl sulfoxide; ELISA, enzyme-linked immunoabsorbent assay; GBM, glioblastoma multiforme; GSC, glioma stem cell; IP, intraperitoneal; OS, overall survival; PI3K/mTOR, phosphoinositide 3-kinase/ mammalian target of rapamycin; PO, per os, by mouth; TUNEL, terminal deoxynucleotidyl transferase dUTP nick end labeling; VM, vasculogenic mimicry; NF-kB, Nuclear Factor kappa-light-chain-enhancer of activated B cells; JNK, c-Jun N-terminal kinase; STAT3, Signal transducer and activator of transcription 3.…”
Section: Introductionmentioning
confidence: 99%
“…Gain of fat mass is significantly and independently associated with declining physical performance as well as an increased risk for disability, hospitalizations, and mortality in older individuals. This increased fat mass is not exclusively stored in adipose depots but may become deposited in non-adipose tissues [27]. Our study found that a significant weight gain (Fig.…”
Section: Effects Of Efandllf On Body Weight Blood Lipids and Liver Funmentioning
confidence: 47%